Implementasi Pembelajaran Berdiferensiasi dan Dampaknya Terhadap Motivasi Belajar Bahasa Inggris pada Siswa MTSN Semarang - Rochma, Nanda Muntia Nur; Nejatullah, Alfa; Nisa, Jana Khairun; Lestari, Wahyu Putri; Maharani, Suesthi (Jurnal Inovasi Pembelajaran di Sekolah, 2025)
This study aims to address low English learning motivation among eighth-grade students at MTsN Semarang through the implementation of differentiated instruction adapted to students’ readiness levels, interests, and learning profiles. The research examines how differentiated instruction was implemented and evaluates its impact on students’ motivation within a heterogeneous classroom context. A descriptive qualitative approach was employed, using open-ended questionnaires and in-depth interviews with five students representing diverse learner profiles and one eighth-grade English teacher. Data were analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings indicate that differentiated practices supported by diagnostic assessment, varied learning activities, task options, and multimodal learning media significantly enhanced students’ engagement, confidence, and motivation in learning English. The study concludes that differentiated instruction is an effective and contextually relevant strategy to improve English learning motivation at the junior secondary level and aligns well with the Merdeka Curriculum’s emphasis on adaptive, student-centered learning.